Reduction of Fe(III) oxides by phylogenetically and physiologically diverse thermophilic methanogens. Issue 3 (30th June 2014) - Yamada, Chihaya; Kato, Souichiro; Kimura, Satoshi; Ishii, Masaharu; Igarashi, Yasuo
Abstract Three thermophilic methanogens (Methanothermobacter thermautotrophicus, Methanosaeta thermophila, and Methanosarcina thermophila) were investigated for their ability to reduce poorly crystalline Fe(III) oxides (ferrihydrite) and the inhibitory effects of ferrihydrite on their methanogenesis. This study demonstrated that Fe(II) generation from ferrihydrite occurs in the cultures of the three thermophilic methanogens only when H2 was supplied as the source of reducing equivalents, even in the cultures of Mst. thermophila that do not grow on and produce CH4 from H2/CO2. While supplementation of ferrihydrite resulted in complete inhibition or suppression of methanogenesis by the thermophilic methanogens, ferrihydrite reduction by the methanogens at least partially alleviates the inhibitory effects. Microscopic and crystallographic analyses on the ferrihydrite‐reducing Msr. thermophila cultures exhibited generation of magnetite on its cell surfaces through partial reduction of ferrihydrite. These findings suggest that at least certain thermophilic methanogens have the ability to extracellularly transfer electrons to insoluble Fe(III) compounds, affecting their methanogenic activities, which would in turn have significant impacts on materials and energy cycles in thermophilic anoxic environments.